2013
DOI: 10.1038/srep02959
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Prediction of Electronic Potentials of Single-Walled Carbon Nanotubes With a Specific Chirality (n,m)

Abstract: The determination of the electronic states of single-walled carbon nanotubes (SWNTs) with a specific chirality has been a central issue in the science of SWNTs. Here we present the empirical equations with fitting parameters for the determination of the reduction and oxidation potentials of SWNTs for a wide range of diameters and chiral angles. In these equations, a distinct chirality family dependence of the reduction potentials is observed, while the oxidation potentials show a simple diameter dependence nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…As shown in Fig. 4h, sem-SWNTs with (n,m) ¼ (6,5), (7,5), (7,6), (8,3), (8,4), (8,6), (8,7), (9,4), (9,5), (9,7), (10,2), (10,3), (10,5), (10,6), (11,3), (11,4), (11,6) and (12,2) were found to exist in the solution. In order to evaluate the extraction efficiency for each (n,m) chirality of the tubes, we calculated the relative contents of each SWNT based on the calibrated PL intensity using the method reported by Oyama et al 57 The calibrated contents of the SWNT species deduced from the PL mapping are shown in Supplementary Table 1, in which SWNTs with (n,m) ¼ (7,6), (8,6), (9,4) and (10,2) were enriched for the sample using CP-Zn.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 4h, sem-SWNTs with (n,m) ¼ (6,5), (7,5), (7,6), (8,3), (8,4), (8,6), (8,7), (9,4), (9,5), (9,7), (10,2), (10,3), (10,5), (10,6), (11,3), (11,4), (11,6) and (12,2) were found to exist in the solution. In order to evaluate the extraction efficiency for each (n,m) chirality of the tubes, we calculated the relative contents of each SWNT based on the calibrated PL intensity using the method reported by Oyama et al 57 The calibrated contents of the SWNT species deduced from the PL mapping are shown in Supplementary Table 1, in which SWNTs with (n,m) ¼ (7,6), (8,6), (9,4) and (10,2) were enriched for the sample using CP-Zn.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
“…Not only their structural characteristics, but also opto-electronic properties derived from their diameters and chiral indices, denoted as (n,m)SWNTs, are important for a deep understanding of their fundamental intrinsic properties [1][2][3][4][5][6][7][8][9][10] . Highly purified semiconducting SWNTs (sem-SWNTs) not containing metallic SWNTs (met-SWNTs) are specifically required for electronic devices, such as field-effect transistors [11][12][13][14] and photovoltaic applications 15,16 because the met-SWNTs decrease and reduce the efficiency of their associated devices 17,18 .…”
mentioning
confidence: 99%
“…[13][14][15] The PL signals from the SWNTs are originated from the exciton of the isolated SWNTs, which has been well-known in the carbon nanotube science. We Finally, we described the construction of highly durable fuel cells based on carbon nanotubes as the material, which is highly important for the next generation fuel cells.…”
Section: Electrochemistry Of Carbon Nanotubesmentioning
confidence: 99%
“…At the same time, in this study, we determined the redox states of the (6,4)-and (9,1)-SWNTs whose diameters are 0.692 and 0.757 nm, respectively. Based on our previously reported data on redox potentials of 15 different (n, m)-SWNTs [30] and those of the 3 mentioned SWNTs measured in this study, we have succeeded to present chirality family dependent empirical equations that correlate the reduction (E red ) and oxidation (E ox ) potentials, Fermi levels (E F ) and work functions (WF) of the (n, m)-SWNTs with a wide range of tube diameters [75]. As shown in Fig.…”
Section: Empirical Prediction For Electronic Potentials Of Swntsmentioning
confidence: 99%